2005
DOI: 10.1002/marc.200500640
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Free Radical Polymerizations and Copolymerizations of Styrene and Methyl Methacrylate

Abstract: Summary: Radical homopolymerizations and copolymerizations of styrene were performed in toluene and N,N‐dimethylformamide (DMF) as solvents using different initiators with and without microwave irradiation. Only the homopolymerization of styrene under microwave irradiation in DMF with DtBP showed significantly enhanced styrene conversion whereas other initiators resulted in no or only slight increase of styrene conversion under microwave irradiation. In any case, DMF was required to gain in styrene conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 5 publications
2
30
0
1
Order By: Relevance
“…[42] Free Radical Copolymerizations Greiner and coworkers investigated the free radical polymerization of styrene and copolymerization of styrene and MMA with and without MW irradiation (monomode MW reactor, temperature control) by using different organic peroxide initiators in a solution of toluene and N,N -dimethylformamide (DMF). [44] It was found that the homopolymerizations of styrene in DMF showed a significantly higher monomer conversion under MW conditions compared with experiments performed in an oil bath. However, the conversions of polymerizations performed in toluene were not influenced by MW irradiation.…”
Section: Free Radical Homopolymerizationmentioning
confidence: 98%
“…[42] Free Radical Copolymerizations Greiner and coworkers investigated the free radical polymerization of styrene and copolymerization of styrene and MMA with and without MW irradiation (monomode MW reactor, temperature control) by using different organic peroxide initiators in a solution of toluene and N,N -dimethylformamide (DMF). [44] It was found that the homopolymerizations of styrene in DMF showed a significantly higher monomer conversion under MW conditions compared with experiments performed in an oil bath. However, the conversions of polymerizations performed in toluene were not influenced by MW irradiation.…”
Section: Free Radical Homopolymerizationmentioning
confidence: 98%
“…Solvent effects for free-radical polymerizations were investigated in detail by Greiner and coworkers. [15,16] Given the example of the tert-butyl perbenzoate (tBPB)-initiated radical copolymerization of styrene and methyl methacrylate (MMA), no significant effects were observed in toluene, but in DMF. tBPB was the initiator with the lowest decomposition rate of all peroxides investigated in this comparative study, comprising also dibenzoyl peroxide and dicumyl peroxide.…”
Section: Free-radical Polymerizationsmentioning
confidence: 98%
“…Hence six different homopolymers of myristyl acrylate, P-1, P-2, P-3, P-4, P-5, and P-6 correspond to reaction times 25, 20, 15, 10, 8, and 2 min, respectively, are obtained (Stange et al, 2006).…”
Section: Microwave-assisted Polymerizationmentioning
confidence: 99%